2005
DOI: 10.1100/tsw.2005.60
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Arsenic with Zinc and Organics in a Rice (Oryza sativaL.)–Cultivated Field in India

Abstract: A laboratory experiment on an Inceptisol with pH 7.6, organic carbon 6.8 g kg-1, and 0.5 M NaHCO3 extractable arsenic 0.4 mg kg-1 was conducted to study the interaction effect of graded levels of arsenic (0, 5, and 10 mg kg-1) with zinc (0, 10, and 20 mg kg-1) and organics (0, 1, and 2% on soil weight basis) separately on the mobilization of arsenic in soils.The results show that the amount of 0.5 M NaHCO3 extractable arsenic at pH 8.5 increased with the progress of submergence up to 35 days. However, the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The phytotoxicity of arsenic is expected to be greater in sandy soils than in other types of soil, since sandy soil usually contain low amount of Fe and Al oxides and clays. Irrigation water, soils and plants from adjacent rice and wheat fields were analysed for arsenic and other elements and showed that rice and wheat grains were not contaminated by arsenic, but concentrations in rice roots exceeded 160 mg/kg due to an Fe-rich plaque around rice roots (Das et al 2005, Norra et al 2005). …”
Section: Effects Of Graded Doses Of Arsenic Exposure To Ricementioning
confidence: 99%
See 1 more Smart Citation
“…The phytotoxicity of arsenic is expected to be greater in sandy soils than in other types of soil, since sandy soil usually contain low amount of Fe and Al oxides and clays. Irrigation water, soils and plants from adjacent rice and wheat fields were analysed for arsenic and other elements and showed that rice and wheat grains were not contaminated by arsenic, but concentrations in rice roots exceeded 160 mg/kg due to an Fe-rich plaque around rice roots (Das et al 2005, Norra et al 2005). …”
Section: Effects Of Graded Doses Of Arsenic Exposure To Ricementioning
confidence: 99%
“…The highest accumulation of arsenic was recorded in roots compared to stems, leaves and grains; it might be caused by As mobility within the plant, which would support the results reported by Liu et al (1985) who showed the distribution of arsenic in plants in the descending order (root > stem > leaf > edible part). Das et al (2005) reported that the accumulation of arsenic in rice root, stem, leaves and grains might be significantly decreased with the application of Zn, by management of irrigation water, or both. The values recorded in individual plant parts with the application of Zn under intermittent ponding throughout the growth period of rice compared to other water management practices were as follows: roots (7.15 mg/kg), stem (5.14 mg/kg), leaf (5.49 mg/kg) and grain (0.81 mg/kg).…”
Section: Effects Of Graded Doses Of Arsenic Exposure To Ricementioning
confidence: 99%
“…Correspondingly, it was reported that the toxicity of arsenic may be reduced by applying sulfates of zinc, iron and aluminum to the soil [28]. An increase in arsenic concentration was correlated with decreasing application of graded levels of Zn as Zn-sulfate was also reported [29].…”
Section: Resultsmentioning
confidence: 91%
“…The addition of OAs potentially increases (Xie and Huang 1998;Suda et al 2015) and decreases (Das et al 2005) dissolved As through a variety of mechanisms (see ''Introduction'' section). The present study showed different effects of three types of OAs on As solubility.…”
Section: Implication and Further Studiesmentioning
confidence: 99%
“…Organic matter potentially insolubilizes As through several mechanisms, such as binding of As with phenolic OH, carboxylate, and sulfhydryl groups with/ without ternary complex (cation bridging) (Thanagalasingam and Pickering 1986;Buschmann et al 2006;Langner et al 2011). Das et al (2005) reported the decrease in sodium hydrogen carbonate-extractable As during submerged soil incubation with a well-decomposed farm yard manure and vermicompost. Rahaman et al (2011) found that the application of OAs, and their combination, significantly decreased the As load of rice plants.…”
Section: Introductionmentioning
confidence: 99%